Work-Related Accidents and Their Predictors Among Delivery Drivers in Egypt: A Cross-Sectional Study - Yousef, Omnia Ahmed Mahmoud; El-Helaly, Mohamed; El-Wehedy, Adel; Denewar, Khadija Abdel Fattah (La Medicina del Lavoro, 2026)
Background: The rapid growth of the delivery sector, driven by online shopping and the COVID-19 pandemic, has raised safety concerns for delivery drivers, particularly work-related accidents and injuries. This study aimed to estimate the frequency of work-related accidents and injuries among delivery drivers and to identify potential predictors associated with these accidents in Egypt. Methods: A descriptive cross-sectional study with an analytical component was conducted among 172 delivery drivers recruited from gathering areas in Mansoura, Egypt. Participants were interviewed using a semi-structured questionnaire. Results: Among participants, 57.0% reported at least one work-related road accident during their career, with most accidents (91.8%) resulting from collisions with other vehicles. All injured drivers sustained at least one post-accident injury, most commonly contusions (93.9%). The lower limbs were the most frequently affected body parts (80.6%). After adjusting for confounders, the multivariable logistic regression analysis revealed that the following workplace exposure factors were significantly independent predictors of work-related accidents: being a university student or graduate (AOR = 2.86, 95% CI: 1.35-6.08), having more than five years of driving experience (AOR = 4.62, 95% CI: 2.15-9.94), and using mobile phones while driving (AOR =3.22, 95% CI: 1.56-6.64). Conclusions: This study showed a high frequency of work-related road accidents among delivery drivers in Egypt. Key predictors included higher education, extensive driving experience, and mobile phone use while driving. These findings underscore the need for targeted interventions, including safety training, regulation of mobile phone use, and awareness campaigns, to mitigate accident risk among delivery drivers.